Uptake of telehealth in Parkinson's disease clinical care and research during the COVID-19 pandemic. (May 2021) - Shivkumar, Vikram; Subramanian, Thyagarajan; Agarwal, Pinky; Mari, Zoltan; Mestre, Tiago A.; ,
Abstract: Introduction: Traditionally, medical care and research in Parkinson's disease (PD) have been conducted with in-person encounters. The recent COVID-19 pandemic has profoundly impacted the delivery of in-person clinical care and clinical research. We conducted an online survey of active clinician members of the Parkinson Study Group (PSG) to evaluate the adoption of various non-face-to-face methods in clinical practice and research in PD during the COVID-19 pandemic. Methods: We conducted a survey using the open-access online SurveyMonkey tool (http://www.surveymonkey.com ). The survey had 27 items and was designed to elucidate clinical/research care before and during the COVID-19 pandemic. The survey was sent to 414 active PSG members with weekly reminders and it remained accessible for 30 days from May 2020. Results: We received 142 responses, of which 133 (93.7%) provided demographic data. The clinical use of virtual visits via synchronous video conferencing increased from 39.5% pre-COVID-19 to 94.6% during the COVID-19 pandemic. Lack of access for patients (68.2%) and patient resistance (51.4%) were the top barriers for its use. Approximately 70% respondents stated that 75–100% of their research activities were suspended during the COVID-19 pandemic. Many sites had to fill out protocol deviations (38.2%), protocol exceptions (25.5%) or change their research profile due to layoffs (16.8%). The overall use of video conferencing increased from 30.3% to 64.1%. Conclusion: The current results suggest a need for flexibility in conducting office visits and clinical trials in PD patients. Technology has the potential to enhance patient care and convenience, when in-person visits can be challenging. Highlights: The COVID-19 pandemic has impacted the delivery of in-person care and clinical research. The uptake of telehealth for clinical visits and research increased during the pandemic. Lack of access for patients and patient resistance were the top barriers to the uptake of telehealth. Technology has the potential to enhance patient care & convenience.